A Hydrodynamic Study in a Sieve Plate Sectionalized Bubble Column - Burhan Sadeq Abdulrazzaq (Engineering and Technology Journal, 2011)
The sectionalization of conventional bubble columns to tray bubble column by perforated trays has been used in chemical, biochemical, and petroleum processes as an effective way to improve the gas-liquid contacting efficiency, and reduce liquid backmixing. In this study, an experimental semi-batch tray bubble column setup has been built. Column 0.15 m inside diameter and total height of 2.20 m is sectionalized into four stages using three perforated plates to investigate the effect of tray geometry, superficial gas velocities and liquid phase physical properties on overall gas holdup. The overall gas holdup is measured experimentally by bed expansion technique. For studying the effect of physical properties of the liquid phase, two different gas and liquid systems are used (airwater and air-methanol solution).Methanol solution was used as the liquid phase to simulate the hydrodynamic behavior of the high gas holdup systems. Remarkable increases of up to 80% in the overall gas holdup have been observed in tray column as compared to conventional bubble column when this liquid system was used. Experimental results of tray bubble column shows significant increase the overall gas holdup in comparison with conventional bubble column. Correlations have been used for the estimation of the fractional gas holdup in bubble column with and without tray. Comparison of the model predictions with the experimental data and with the published data of other authors shows fine agreement which ensure the reliability and confidentiality of the adopted the correlations to be used in further designation.